Aqueous two-phase extraction and polyelectrolyte precipitation combination: A simple and economically technologies for pepsin isolation from bovine abomasum homogenate - Boeris, Valeria (2009)
The combination of two bioseparation techniques, partition in aqueous two-phase systems and polyelectrolyte precipitation of the target enzyme from the phase where it is present, was assayed to purify pepsin from bovine abomasum homogenate. Pepsin was partitioned in favor of the polyethyleneglycol-rich phase in an aqueous two-phase system of polyethyleneglycol 600 and 1450-sodium phosphate; however, a great amount of impure proteins were present. Chitosan (a cationic natural polyelectrolyte) was added to precipitate this acid enzyme as a form of insoluble complex. The addition of this second step increased the purity of the enzyme significantly while the yield was not significantly decreased. The combination of both partition in polyethyleneglycol 1450-phosphate system and chitosan precipitation produced a pepsin recovery of 48.5% with a purification factor of 9.0. The biological activity of the recovered enzyme remained unaltered.